The Socio-Economic Impact of Syrian Refugees on the Local Communities in Mafraq Governorate / Jordan: Sociological Field Study - Atiyat, Fatima (Jordan Journal of Social Sciences, 2018)
Jordan is profoundly affected by the influx of over 1.4 million Syrians among them 655,000 registered refugees. Today, Jordan is struggling to provide housing, education, healthcare, and jobs to its increased communities and this enormous numbers of Syrian refugees. The study aims at understanding the socio-economic impact of refugees on Mafraq governorate. It used the Social Survey method with a sample consisted of 420 respondents randomly chosen from different geographical locations of the governorate. The study revealed that local communities first welcomed Syrians, offered jobs, and established good relationships with refugees. However, local communities in Mafraq became wearier of Syrians, as the two groups have to compete over such scarce socio-economic resources, such as jobs, education, health service and other infrastructures. The study recommends more international aid to Jordan to enable the country to provide various services to its communities including refugees to aid in coping with difficult circumstances.